Contribution of Iraqi women in development: from the perspective faculty members to the complex Jadiriyah/University of Baghdad (Journal of the College of Education for Women, 2019)
The researchers in this study, which aimed to find out Degree contribution of Iraqiwomen in development from the perspective faculty members of the complex JadriyaUniversity in Baghdad, and the the impact of demographic variables (gender, college, place ofliving, school level,) for its contribution.The study population consisted of some faculty members Jadiriyah compound inBaghdad's University for the academic year 20012/2013. This study followed a descriptiveapproach the field, and the analytical method, the study sample consisted of (250) teaching allof College of Science for girls and education for girls, and to achieve objective of the studywas the development of a questionnaire, was sure of its sincerity and the coefficient ofstability, was calculated reliability coefficient by Cronbach's alpha equation "was ((81.3%)which meeting the objectives the study. after the process of collecting questionnaires, havebeen coded and entered into a computer and processed statistically. using the statisticalpackage is SPSS. The study revealed the following results:1-There were no statistically significant differences at the level of significance (@ = 0.05) ofthe contribution of Iraqi women in development from the perspective faculty members atthe University of Baghdad attributed to the place of living qualification variables.2-All fields of study got great approval with the exception of domestic the field, as earned hada moderate consent.It was presented a number of recommendations to improve the contribution of Iraqiwomen in development.